Price-minimizing behaviors in response to increasing tobacco price: a cross-sectional study of students - Rutter, Lucy; Britton, John; Langley, Tessa (Taylor & Francis (Routledge), 2017)
Background: The public health benefits of tobacco taxation are undermined when smokers engage in price-minimising behaviours other than quitting in response to rising prices. These include switching from smoking manufactured cigarettes to cheaper alternatives such as roll your-own (RYO). Young adults are particularly sensitive to tobacco prices. Methods: 314 students at the University of Nottingham, UK completed an online survey about their current smoking behaviour and their likely responses to hypothetical increases in the price of tobacco. Results: Cessation intent was linked to price, as was the likelihood of switching to cheaper products. Although only 7% said they would quit in response to a £0.50 increase in the price of their product, 68% said they would quit if it doubled. Among manufactured cigarette smokers who would switch products if the price of cigarettes doubled, 33% said they would switch to RYO. 44% stated they would switch to e-cigarettes if combustible tobacco became unaffordable. Conclusions: Large price increases could reduce prevalence among this age group, though this effect would be potentially be undermined by young adult smokers accessing cheaper alternatives to manufactured cigarettes. The apparent viability of e-cigarettes as a price minimising substitute for smoking may be encouraging from a public health perspective.